PENYULUHAN LITERASI MEDIA DAN ETIKA DIGITAL BAGI MAHASISWA MELALUI PELATIHAN DARING INTERAKTIF - Yati Bt Samsuddin; Andry Priyadharmadi Purnama; Buya Hamka; Nurjayanti Nurjayanti (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
The high level of digital media usage among university students is not always accompanied by sufficient media literacy or awareness of digital ethics. Many students engage in sharing unverified information, using inappropriate language on social media, and demonstrating limited understanding of privacy and copyright principles. To address these issues, a community service activity was conducted in the form of an interactive online workshop titled "Media Literacy and Digital Ethics Awareness for University Students." The goal was to enhance students' critical and ethical awareness in digital media usage. The training was held via Zoom and attended by 40 students from various disciplines. Quantitative evaluation was conducted through satisfaction surveys and pre-test/post-test comparisons, while qualitative evaluation involved observing participant interactions during the sessions. Results indicated a significant increase in understanding, with the proportion of students categorized as “highly understanding” rising from 10% to 45%. Satisfaction responses showed that the majority of participants found the materials highly relevant and beneficial. These findings suggest that online-based outreach programs are effective strategies for fostering digital literacy and ethical awareness among students from diverse academic backgrounds.Keywords: media literacy, digital ethics, university students, online training, outreach